FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BBLR DI RSUD SYEKH YUSUF KABUPATEN GOWA - andi khairul musyawir (Stikes Graha Edukasi Makassar, 2020)
Objective: To know the Factors related to the LBW incidence in RSUD Syekh Yusuf Gowa District. Method: The type of research used in this study used is an analytic survey research using Cross Sectional Study approach where the variables associated with the occurrence of BBLR observed simultaneously in the same time, Results: The results showed that the mother's age was not associated with the occurrence of LBW, Distance labor is not related to the occurrence of LBW, Nutritional status is not related to the occurrence of LBW, this is proved by the value p> ? (0.05), Discussion: The birth of a baby with LBW is an indicator to assess the extent of a child's growth and the readiness of human resources in the future. Conclusion: Age, gestational distance, maternal status during pregnancy is not related to LBW occurrence